Oligochitosan-pluronic 127 conjugate for delivery of honokiol. (31st October 2018) - Song, Zhimei; Sun, Jingjie; Deng, Peizong; Zhou, Feilong; Xu, Hongmei; Wen, Yi; Teng, Fangfang; Ge, Di; Feng, Runliang
Abstract: Honokiol-loaded micelles were prepared by emulsion-solvent evaporation procedure when oligochitosan-pluronic conjugate (CS-F127) as carrier. Differential scanning calorimetry (DSC) indicated that honokiol existed in amorphous form when it was encapsulated into the micelles with 87.54 ± 1.52% of encapsulation efficiency (EE) and 12.51 ± 0.22% of drug loading (DL) capacity. The water-solubility was increased to 1.46 mg/mL, being >27-folds higher than pure honokiol. The in vitro release study demonstrated a slow and sustained ± release of honokiol from the drug-loaded micelles with pure honokiol as control. The in vitro antifungal and cellular uptake tests indicated that the drug-loaded micelles showed the same activity as pure honokiol against Candida albicans due to its good cellular uptake although it slowly released honokiol. The pharmacokinetic test results showed that the honokiol-loaded micelles increased area under curves and mean retention time of honokiol with low clearance rate and apparent distribution volume when compared with pure honokiol, showing its ability to improve honokiol's pharmacokinetic properties. The honokiol-loaded micelles also showed good bio-security to normal cells and main organs of mice. In conclusion, the CS-F127 conjugate should be a potential carrier for honokiol or other antifungal agents in the treatment of fungal infections.